Pregunta
Solving for a variable in terms of other variable Solve for \( Z \). \( X=\frac{5}{6}(Y-Z) \) \( Z=\square \)
Ask by Grant Williams. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( Z = Y - \frac{6}{5} X \)
Solución
To solve for \( Z \) in the equation:
\[
X = \frac{5}{6}(Y - Z)
\]
follow these steps:
1. **Multiply both sides by \( \frac{6}{5} \)** to eliminate the fraction:
\[
\frac{6}{5} X = Y - Z
\]
2. **Isolate \( Z \)** by subtracting \( Y \) from both sides:
\[
\frac{6}{5} X - Y = -Z
\]
3. **Multiply both sides by \( -1 \)** to solve for \( Z \):
\[
Z = Y - \frac{6}{5} X
\]
**Final Solution:**
\[
Z = Y - \frac{6}{5} X
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To solve for \( Z \), you'll want to isolate it on one side of the equation. Start with \( X = \frac{5}{6}(Y - Z) \). Multiply both sides by \( \frac{6}{5} \) to eliminate the fraction: \[ \frac{6}{5}X = Y - Z. \] Now, to isolate \( Z \), simply rearrange the equation: \[ Z = Y - \frac{6}{5}X. \] And there you have it! \( Z = Y - \frac{6}{5}X \). Keep in mind that rearranging equations is like a puzzle; always double-check your operations to ensure every piece fits perfectly!
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium